Pemberdayaan Perempuan Korban KDRT Lewat Pendampingan Berbasis Perspektif Gender Di Kota Kupang - Tinenti, Hemma; Siono, Yeremias; Barek Ola, Emilia (Amare, 2022)
The Covid-19 pandemic brought deep sorrow, but it also had quite an intense impact on the economic, social, educational and other situations. Without exception, violence against women has increased quite sharply. This is caused by various factors, one of which is: women who often experience domestic violence do not dare to report and fight. Like the general word they often feel 'knowing'. In addition, there is also a lack of specialization and education for women from the government and the Church or religion. What more if they are housewives and without a job or skill. This is our concern to carry out Community Service activities. In detail, the objectives of this Empowerment activity are: Empowering women victims of domestic violence through mentoring activities. Mentoring here is not spiritual assistance but rather education and increasing knowledge and courage to act without retaliating with violence and solutions to avoid domestic violence. In addition, so that victims are more courageous in expressing their cases without being ashamed of receiving social sanctions, knowing their rights as danita, other impacts are: the development or education of children is disrupted. The assistance in question is: legal, social and spiritual assistance.